2021
DOI: 10.1007/s00221-021-06142-4
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological aftereffects of high-frequency transcranial random noise stimulation (hf-tRNS): an EEG investigation

Abstract: There is evidence that high-frequency transcranial random noise stimulation (hf-tRNS) is effective in improving behavioural performance in several visual tasks. However, so far there has been limited research into the spatial and temporal characteristics of hf-tRNS-induced facilitatory effects. In the present study, electroencephalogram (EEG) was used to investigate the spatial and temporal dynamics of cortical activity modulated by offline hf-tRNS on performance on a motion direction discrimination task. We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…Offline hf-tRNS applied over parieto-occipital cortex was shown to induce moderate aftereffects in γ-range brain oscillatory activity measured with EEG during motion direction discrimination task performance. These physiological effects were, however, not accompanied by behavioral task performance modulation ( Ghin et al, 2021 ). Saito et al (2019) showed that tRNS applied without training, improved tactile spatial discrimination task performance illustrated by a decreased threshold in discriminating grating orientation after 10 min of stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Offline hf-tRNS applied over parieto-occipital cortex was shown to induce moderate aftereffects in γ-range brain oscillatory activity measured with EEG during motion direction discrimination task performance. These physiological effects were, however, not accompanied by behavioral task performance modulation ( Ghin et al, 2021 ). Saito et al (2019) showed that tRNS applied without training, improved tactile spatial discrimination task performance illustrated by a decreased threshold in discriminating grating orientation after 10 min of stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that tRNS achieves after-effects on oscillatory EEG activity [ 242 ], despite its inability to entrain brain oscillations due to its non-rhythmic pattern [ 238 ], supports the abovementioned notion that entrainment may not be required for synaptic plasticity effects of tES.…”
Section: Transcranial Electric Stimulation (Tes)mentioning
confidence: 79%
“…To our knowledge, this is the first randomized, double-blind, sham-controlled clinical trial providing evidence that adjunct hf-tRNS improves negative symptoms of schizophrenia through modulating gamma-band EEG source-based large-scale functional network connectivity. Recent research showed that a single session of hf-tRNS with a low current intensity (1 mA) could modulate brain oscillatory activity within gamma band in healthy human individuals [ 7 ]. There was a lack of evidence for the acute and longer-lasting effects of repetitive hf-tRNS using a protocol comprising 2 mA, 20 min for 10 s (i.e., a total stimulation duration of 200 min) on gamma-band local neural oscillations and long-range functional connectivity in patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Research indicates that tRNS may be the most effective transcranial electrical stimulation (tES) method to increase cortical excitability and thereby elicit behavioral changes [ 6 ]. The high-frequency range (101–640 Hz) of tRNS has been reported to increase neuronal excitability of the stimulated cortex possibly through the repetitive opening of the voltage-gated Na + channels [ 5 ] and modulate event-related gamma-band oscillatory activity [ 7 ] and hemodynamic response of functional stimulus [ 8 ] possibly via the stochastic resonance (SR) that enhances neural signal-to-noise ratio and neuronal synchronization within the stimulated cortex. However, the neural working mechanisms underlying the prompt attenuation of negative symptoms by hf-tRNS over the lateral prefrontal cortex remain to be determined…”
Section: Introductionmentioning
confidence: 99%